Case Report: New insights about clinical manifestations of patients with GCK genetic variants - de Souza, Ritiele Bastos; Abreu, Gabriella de Medeiros; Bernardo, Marília Chaves; Tarantino, Roberta Magalhães; Rodacki, Melanie; Zajdenverg, Lenita; de Andrade, Amanda Ferreira; Nicolay, Deborah Snaider; da Fonseca, Ana Carolina Proença; Salum, Kaio Cezar Rodrigues; Szundy Berardo, Renata; Luescher, Jorge Luiz; et al. (Frontiers in Endocrinology, 2025)
GCK-MODY is a genetic condition characterized by alterations in the GCK gene, which can include several types of inactivating genetic variants - ranging from missense and nonsense variants, and splice site variants, to small and large deletions and insertions in the gene. This disorder primarily affects glucose homeostasis and usually presents in heterozygous individuals. Although GCK-MODY is a well-studied condition, some variant carriers may manifest symptoms that deviate from the typical disease phenotype. Our study identified two Brazilian patients with GCK-MODY carrying novel frameshift variants, one of whom presented atypical manifestations of the disease. The patient is a 14-year-old male harboring a variant c.398del; p.(Phe133SerfsTer7) in the GCK gene. He presented with the typical clinical features of GCK-MODY, including mild and stable fasting hyperglycemia, however, he also presented a history of polyuria and polydipsia, which are unusual symptoms of the disease. These symptoms could be associated with the more severe impact of a frameshift variant. However, we did not observe the same unusual phenotype in our second patient, who is a 15-year-old normal-weight female. At the age of 8, she was diagnosed with diabetes mellitus. The patient with the p.(Val335ArgfsTer124) variant presented with mild, stable hyperglycemia, a characteristic feature of the disease. In this study, we present two cases of novel frameshift variants in GCK and review other reports in the literature that have shown patients with atypical manifestations of the disease and highlight the importance of a comprehensive characterization of the phenotypic spectrum caused by GCK-MODY variants.